Advanced LPCVD ZnO - Challenges in application for thin film solar cells and modules - Messerschmidt, Daniel (My University, 2014)
Ethanol is used as a precursor during the growth of zinc oxide (ZnO) by low-pressure chemical vapor deposition (LPCVD). By adding ethanol, the surface of the deposited ZnO layer is ﬂattened and its roughness is decreased about sevenfold. The layers become increasingly stressed and their resistivity grows signiﬁcantly. The present work proposes an explanation for the observed behavior based on the catalytic decomposition of ethanol at the ZnO surface and on the growth of selected crystal planes. By using ethanol for the last 10 % of the total ZnO layer growth only, sheet resistance is maintained and roughness is slightly decreased. The results indicate that such LPCVD ZnO bilayers could be a promising method to modify the ZnO surface morphology before cell deposition, thus providing an alternative to argon plasma treatment, which is typically reported to improve solar cell parameters such as open-circuit voltage and ﬁll factor.
The introduction of an advanced LPCVD boron-doped ZnO (ZnO:B) into the production line at Bosch Solar Thin Film in Erfurt, Germany, is presented. Here the ZnO:B is deposited with a LPCVD production tool on 1.1 × 1.3 m 2 glass substrates. Early results on a laboratory scale of this advanced transparent conductive oxide (ATCO) type were published by Ding et al. [1,2]. For an ATCO, they combined a highly doped ZnO:B seed layer with a low-doped ZnO:B bulk layer. Compared to a standard ZnO:B (Std-TCO), which is homogeneously doped across the total layer thickness, the ATCO possesses enhanced optical and electrical properties. Comparing the ATCO with the Std-TCO, equal in layer thickness (1800 nm) and sheet resistance (16 to 17 Ω), the ATCO possesses slightly better transmittance. Furthermore, the ATCO showed 37 % haze, which is 3 to 5 % absolute more haze compared to the Std-TCO. After ATCO optimization, a complete micromorph solar module was fabricated, incorporating this new advanced LPCVD ZnO:B layer as the front electrode. An initial module power of 153.7 Wp was achieved. Here the unit Wp indicates that the module was tested under standardized test conditions. The power output was determined at 25 °C with a light illumination power of 1000 W/m2. The light spectrum was adjust to be equivalent to an terrestrial solar spectrum with an air mass 1.5 characteristic.
For the ﬁrst time the present work introduces a novel degradation effect of the ZnO, which is observed for ZnO layers deposited on commercially available soda-lime glass. When an electric ﬁeld is applied, the potential induced anodic degradation causes massive sheet resistance increase of the ZnO. The present work shows that the increase in resistance strongly effects the power output of small non-encapsulated and large encapsulated micromorph thin-ﬁlm photovoltaic modules, in which ZnO was used as the front electrode. The present work proposes that the evolution of gaseous oxygen at the anode (ZnO) may be responsible for the increased resistance of the ZnO. A model that describes this observation is presented and solutions to suppress the effect are proposed. The optical properties of non-degraded and anodically degraded ZnO:B are presented. The optical model used to simulate the infrared reﬂectance in the wavelength range between 1.2 and 25 μm is based on the Maxwell-Garnett effective-medium theory. The model is sensitive to the conditions at the grain boundaries of the investigated polycrystalline ZnO:B ﬁlms. The yielded results conﬁrm the presence of defect-rich grain boundaries, especially after degradation. Furthermore, indications of a degraded ZnO layer next to the ZnO:B/glass interface with a different refractive index are found. Furthermore, based on Raman investigations, evidence for the creation of oxygen vacancies, which correlate with a shift of the optical absorption edge of the ZnO:B, is presented. Investigations with scanning and transmission electron microscopy show microvoids at the grain boundaries after anodic degradation. This indicates that the grain/grain interfaces are the principle location of defects after degradation.
Thèse de doctorat : Université de Neuchâtel, 2014
Keywords: LPCVD zinc oxide; ethanol; diethyl zinc; bilayer; thin-film silicon; micromorph PV module technology; potential induced degradation; PID